Optimasi Konsentrasi NaCl dan Waktu Inkubasi terhadap Kandungan Asam Amino dan Total Padatan Terlarut pada Cacing Tanah (Lumbricus rubellus) dalam Reaktor Anaerob - Hanifah, Windia; Ningrum, Sri Rahayu Widya; Junaidi, Edi (Politeknik ATI Padang, 2025)
In Indonesia, earthworms specifically Lumbricus rubellus are generally underutilized, often used only as fishing bait and not yet fully optimized for their potential as a protein source. This study aimed to optimize the extraction of protein from Lumbricus rubellus using variations in NaCl concentration and incubation time. The extraction process was conducted using the Response Surface Methodology (RSM) with a Central Composite Design (CCD), involving two independent variables: NaCl concentration (3%, 6%, and 9%) and incubation time (24, 48, and 72 hours). The measured responses were dissolved protein, total dissolved solids (TDS), and pH of the extract. The results showed that the optimal condition for protein extraction was at 3% NaCl concentration and 24 hours of incubation, yielding the highest level of dissolved protein. The highest TDS was recorded at 45.5 ppm under the condition of 9% NaCl and 24-hour incubation, while the lowest TDS was 34.3 ppm at 9% NaCl and 72 hours. The pH values ranged from 4.18 to 4.47, with the highest pH observed at 3% NaCl and 24 hours. These findings demonstrate that both NaCl concentration and incubation time significantly influence the efficiency of protein extraction from Lumbricus rubellus, with lower concentrations and shorter times generally producing better results.